Selection of Propulsion System for Electric Amphibious Bus to Alleviate Traffic Congestion in the Jabodetabek Area - Lana, Yuda Safri; Sjamsoeddin, Sjafrie; Ansori, Ansori (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
High vehicle growth in Jakarta is not balanced with traffic growth, the level of congestion in Jakarta continues to increase every year. To overcome this congestion, innovation is needed to utilize the river as a means of public transportation. The amphibious bus is an alternative public transportation option in the Jabodetabek area to break congestion. The amphibious bus design must be supported by a propulsion system that can operate on land and water. The amphibious bus propulsion system is a must, according to river conditions and operational requirements.  The selection of the drive system is carried out by means of analysis The driving criteria factors needed according to the specifications of the amphibious bus are power, efficiency, size, cost, and maneuverability. These criteria become indicators in determining the type of mover. This study aims to select the prime mover system based on criteria and specification requirements. The selection uses the process hierarchy analysis (AHP) method by giving weight to the criteria for each driver, and type of mover in the water, namely waterjets, azimuth-podded, Paddle Wheels, Cycloidal Propellers and propulsion on land diesel engines, gasoline engines, and electric engines. The results showed that the order of the propulsion selection criteria was propulsion power being the top priority, followed by maneuverability, energy efficiency, cost, operational and investment, and propulsion size and weight. The results of the AHP show that the main options are propulsion systems in water, namely waterjets and diesel engine propulsion systems on land. System Water Jet has a propulsion power of 1000 kW, has high maneuverability, energy efficiency of 85%, and a maximum speed of 60 Km/hour so it can meet the specifications of an amphibious bus drive. For operations on land, the main choice of propulsion system for amphibious buses is a diesel engine with a power of 250 HP and 800 Nm of torque providing strong torque and a wide cruising range. This system has a range of up to 800 km, a maximum speed of 120 km/h, and exhaust emissions of Euro 5.